Three essays in applied microeconomics and their implications for policymakers - Ross, Kyle D. (Kansas State University, 2009)
The first essay is on TRIPS (trade related intellectual property rights), biodiversity and North-South trade. This essay explores how true North-South trade and different IPR (intellectual property rights) regimes affect the level of biodiversity that is maintained by a Southern government. The results show that protecting farmers’ rights only is the regime that will be chosen by the Southern government and that will lead to the maximum level of biodiversity. This is important for policymakers as provisions for protecting farmers’ rights do not currently exist. This finding confirms previous results that did not include true North-South trade. Another result, and one that departs from existing literature, is that positive levels of biodiversity will be maintained by the Southern government if only international patent protection is implemented. The second essay focuses on factors that affect attendance at MLS soccer matches, in particular David Beckham. The primary results in the study are that David Beckham has a very large, statistically significant effect on attendance at MLS matches. This effect is estimated as at least a sixty-five percent increase in attendance in games Beckham plays in. Other results from this study are that there are no significant effects from the months matches are played and that the only day of the week with a significant effect is Saturday (its effect is positive). The results from this study provides insight to MLS as it faces upcoming decisions about designated players, such as Beckham, and about the calendar upon which the MLS season is played. The final essay is on moral hazard, market power and the demand for health insurance. The issue of health insurance is one of the main questions facing the U.S. government and its citizens. This essay explores the particular interaction of moral hazard and market power in the form of a duopoly in a pharmaceutical market. The results from this essay show that there are notable differences in the effects on the welfare of market participants under duopoly as compared to monopoly, such as the importance of cross-price effects that do not show up in a monopoly market.
Keywords: Economics; Trade; Sports; Health; Economics, General (0501); Economics, Theory (0511)